Exploring Teacher and Student Interactions in Blended Learning - Anisa, Eka Praja (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2017)
This research aims to describe the exploration of teacher and student interactions in blended learning. This research was conducted at State Elementary School 1/IV Jambi City. This research uses a qualitative approach with a case study type of research. This research data was obtained by observing teacher and student interactions in blended learning, interviews with class IIIa homeroom teachers and students, as well as documentation. The results of this research show that there is interaction between teachers and students in blended learning. The interactions during the learning process based on blended learning are providing students with information, explaining, explaining, directing and telling stories, to encourage students to be active during the learning process, the teacher also asks questions that are remembering, evaluating or understanding. Apart from that, teachers can also give praise, encouragement, and accept students' opinions when students succeed or behave well during the learning process. then the teacher can see the students' responses, how students raise their hands when the teacher asks questions, dare to answer questions, and students also ask questions, express opinions towards the teacher or other students.